Odpowiedzi

2009-11-19T16:43:38+01:00
4y -x = 6
17y=0

4 *0 -x= 6
-x=6 (*-1)
x=-6


a=b
2a+b=9

9/3 = 3
2*3 + 3 +9


u=4v
5u-v=10

5*4V -V=10
19v=10 \19
v= 19/10 =1 9/10


3r=s
3r+s=24

2s=24 /2
s=12
2009-11-19T17:06:57+01:00
Y = 0
x = -6

a = 3
b = 3

r = 4
s = 4



2009-11-19T17:11:19+01:00
4y-x=6
17y=0
17y=0 /17
y=0
4*0-x=6
-x=6
x=-6

x=-6
y=0


a=b
2a+b=9
2*b+b=9
2b+b=9
3b=9
b=3
a=3

a=3
b=3

u=4v
5u-v=10
5*4v-v=10
20v-v=10
19v=10
v=10/19
u=4*10/19
u=40/19

u=40/19
v=10/19

3r=s
3r+s=24
3r+3r=24
6r=24
r=4
3*4=s
s=12

r=4
s=12